E-Nose: An Easier Test for Tuberculosis - Chowdhury, Mostofa Kamal; Sharmin, Tania; Ahasan, HAM Nazmul (Journal of Medicine, 2013)
No Abstract Available. DOI: http://dx.doi.org/10.3329/jom.v14i1.14624 J MEDICINE 2013; 14 : 70-71